Alterações morfológicas decorrentes da expansão urbana no setor leste da cidadede Rio Claro (SP): subsídios ao planejamento urbano - Mendes, Ana Cecilia Pereira [UNESP] (2015)
In medium-sized cities in the São Paulo interior, the urbanization process, occured since 1970, contributed to the occupation of areas likely to trigger morphogenetic processes, causing a series of environmental problems. Thus, the main objective of this research was to identify and analyze the changes generated by urbanization on the relief forms the eastern sector of the city of Rio Claro (SP), through the evolutional historic geomorphological mapping based in antropogeomorfologic approach. From the analysis of these changes, searched to evaluate the restrictions of relief to urban use, considering the dynamic of land use in between of 48 years, to assess the capacity of area to such use. Thus, aimed discuss the consequences of urbanization on morphodynamics of the study area over time, based on the model of stages environmental impacts proposed by Nir (1983), which seeks to demonstrate the influence of urbanization on morphodynamics, (pre-urban period, construction period and developed urban period). Therefore, elaborated the Environmental Fragility Map from the information extracted of the slope map, unconsolidated materials map and geomorphological maps of different scenarios (1962, 1972, 1988, 1995 and 2010). The data extracted from this maps, together with the land use maps of scenarios from 1962, 1972, 1988, 1995 and 2010 were used for the construction of Restrictions levels to Use Urban Map. The geomorphological maps and land use maps, with historical and evolutionary character, supported the analysis of the transformations that have occurred in relief over time. Thus, the urbanization in the study period (48 years) was responsible for creating diverse anthropogenic geomorphological features, such as topographic rupture anthropic, artificial canals and channeled hydrography, and also modified natural processes of perennial and temporary rivers (energy of the channel and quantity of transported sediment) and the hillside ...